RANCANG BANGUN MODEL PEMBELAJARAN BAHASA INGGRIS INTERAKTIF BERBASIS MULTIMEDIA - Romodon, Dion; Kusrini, Kusrini; Fatah, Amir (Jurnal Ilmiah Among Makarti, STIE AMA Salatiga, 2013)
Abstract This research aims to design an English learning program based interactive multimedia learning resources and quality as an alternative media that can be used to increase student motivation and understanding shown by national test scores of English.The try-out subjects in this study are 71 students as respondent. There are two experts, consisting of matter experts and media expert. Beside that there are 10 students for the test user. The data was collected using a questionnaire and English test (pre-test and post-test). Evaluation of the program in terms of aspects, and aspects of learning media.Criticisms and suggestions are used to improve the program.The results showed that the development of multimedia learning has been using the principles of development which include: analytics, product development, validation, revision, testing and preparation of the final product. Multimedia quality in terms of material aspects including the excellent category with 89.59% votes. Quality of multimedia instructional media experts including the excellent category with 94.47% votes. Test English with through pre-test and post-test which was built through the program show an increase in mastery learning. 89.33% for manual assessment and students 85.84%. Increased scores indicate that the learning programs improve student learning outcomes for national test preparation. Key word: desain model,Interactive,multimedia,learning English,Adobe Flash